Understanding the Crime of Money Laundering in the Concept of Criminal Law in Indonesia - Muhammad Ridwan Lubis; Cut Nurita (Faculty of Law, Universitas Pekalongan, 2023)
Nowadays, the patterns and behaviors of Money Laundering constitute efforts to conceal or disguise the origin of money or wealth resulting from criminal activities through various financial transactions, making the money or wealth appear as if it comes from legal activities. Several common or frequent actions are taken in the process of committing money laundering to